HUBUNGAN KARAKTERISTIK DAN PENGETAHUAN IBU TENTANG GIZI DENGAN KEJADIAN STUNTING PADA BALITA USIA 12-59 BULAN DI UPTD.PUSKESMAS NUSA PENIDA I - Dwijayanti, Yuke; Nurtini, Ni Made; Dewi, Ni Wayan Erviana Puspita (JURNAL MEDIKA USADA, 2024)
Background: The prevalence of stunting incidence based on weighing operations in Februari 2022 on toddlers aged 12-59 months in the working area of Public Health Center I Nusa Penida is above the average of stunting rate in Bali in 2021which was 24.61%. The causes of stunting are mothers’ characteristics such as age, education, occupation, family income, and mother’s knowledge about nutrition. Purpose: To identify the correlation between characteristics and mothers’ knowledge about nutrition and stunting incidence on toddlers aged 12-59 months in the working area of Public Health Center I Nusa Penida. Method: This study employed analytical quantitative design with cross sectional approach. The sample of this study was 312 mothers which were chosen by using probability sampling technique. The data were analyzed by using bivariate with chi square test. Findings: Based on statistical test with chi square test showed that there was significant correlation between mothers’ age (p=<0,001), knowledge level (p=<0,001), and income (p=0,000) toward stunting incidence on toddlers aged 12-59 months. There was not correlation between mothers’ occupation, parity, and mothers’ knowledge about nutrition toward stunting incidence on toddlers aged 12-59 months. Conclusion: It can be concluded that most of toddlers aged 12-59 months do not experience stunting. Having child in the vulnerable age (<20 and >35 years), education level, and income has correlation with stunting, meanwhile parity and knowledge level do not have correlation with stunting.